Unraveling the Destruction of Nature Based on Sallie McFague's View "The Universe is the Body of God" - Nainggolan, Diana (Jurnal Teologi Trinity, 2023)
Anthropocentrism is usually accused of being the cause of the birth of hierarchical relations between humans and other non-human creatures. Humans are placed at the center of everything and gain legitimacy as rulers of the universe and have an impact on the destruction of nature. Humans are required to change their perspective and behavior towards nature to save nature from further damage. This article aims to formulate a new metaphor of nature from Sallie McFague’s metaphor that the world (universe) is the body of God as an effort to maintain the sustainability of life inside the body of God. This research is carried out by reviewing literatures that are relevant. Based on the research, it was found that viewing nature as the body of God can raise awareness to preserve forests.